Reaproveitamento de resíduos industriais de inseticidas em processos anaeróbios de geração de biogás - Bortolucci, Ana Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Biogas can be considered a potential biofuel, as it is mainly composed of methane gas, carbon dioxide and hydrogen. It is the product of anaerobic digestion, where industrial waste can serve as a substrate, because they have readily assimilable organic matter. Among these, the industrial residues of insecticides, contain toxic chemical constituents such as Hidrametilnona, Imidaclopride, Indoxacarbe, among others. Thus, this work aimed to evaluate the biogas generation potential in batch anaerobic reactors from residues from insecticide industries. Three phases were performed: Preliminary test with inoculum sources from mesophilic sludge from UASB reactors; Characterization of industrial waste and Operation of anaerobic reactors in batch to obtain biogas, where reactors with 20% of inoculum, modified PYG medium, pH 7.0, 37°C and headspeace with N2 (100%). All the inoculums tested produced biogas and methane gas, the best inocula were those of aviculture. For cultures with PYG and sodium acetate medium, the best concentrations were for 2 g of carbon source.1-1. The industrial residue had acid pH, high concentrations of organic matter, about 75 g COD.l-1, and a predominance of acidophilic bacilli. In all the anaerobic reactors, the organic matter was converted into biogas, producing methane gas at high concentrations and presenting acidophilic bacilli and filamentous bacteria. In the condition with 100% of culture medium, 81% of COD were consumed and 77% of methane gas was obtained in the headspace

O biogás pode ser considerado um potencial biocombustível, pois é constituído principalmente por gás metano, dióxido de carbono e hidrogênio. É produto da digestão anaeróbia, onde resíduos industriais podem servir como substrato, por terem matéria orgânica prontamente assimilável. Dentre estes, os resíduos industriais de inseticidas, contém constituintes tóxicos químicos, como Hidrametilnona, Imidaclopride, Indoxacarbe, dentre outros. Deste modo, este trabalho visou avaliar o potencial da geração de biogás em reatores anaeróbios em batelada a partir de resíduos de indústrias de inseticidas. Foram realizadas três etapas: Teste preliminar com as fontes de inóculo provenientes de lodos mesofílicos de reatores UASB; Caracterização do resíduo industrial e Operação dos reatores anaeróbios em batelada para obtenção do biogás, onde foram usados reatores com 20% de inóculo, meio PYG modificado, pH 7,0, 37°C e headspeace com N2 (100%). Todos os inóculos testados produziram biogás e gás metano, os melhores inóculos foram os de aviculturas. Para os cultivos com meio PYG e acetato de sódio, as melhores concentrações foram para 2 g de fonte de carbono.l-1. O resíduo industrial apresentou pH ácido, elevadas concentrações de matéria orgânica, cerca de 75g DQO.l-1, e predomínio de bacilos acidófilos. Em todos os reatores anaeróbios houve a conversão da matéria orgânica em biogás, produzindo gás metano em elevadas concentrações e apresentando bacilos acidófilos e bactérias filamentosas. Na condição com 100% de meio de cultivo foram consumidos 81% de DQO e obteve-se 77% de gás metano no headspace
Keywords: Engenharia ambiental; Residuos industriais - Aspectos ambientais; Biogas; Metano; Digestão anaeróbia